2020
DOI: 10.3390/genes11020161
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Transcriptome Analysis of Volvariella volvacea Identified the Candidate Genes Involved in Fast Growth at the Mycelial Growth Stage

Abstract: The edible straw mushroom, Volvariella volvacea, is one of the most important cultivated mushrooms in tropical and sub-tropical regions. Strain improvement for V. volvacea is difficult because of the unknown mechanisms involved in its growth regulation and substrate utilization. A comparative physiological and transcriptomic study was conducted between two commercially available straw mushroom strains (v9 and v26) to explore their fast-growth regulation mechanism(s). The physiological study showed that V. volv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Volvariella volvacea (Bulliard ex Fries) Singer, 1951, also known as "rice mushroom", "straw fungus" or "Chinese mushroom", is a species found in tropical and subtropical climates (Liu et al, 2020). Its cultivation is believed to have originated in China, possibly before the 18th century (Chang, 1977), and has been used due to its high concentrations of nutrients and bioactive compounds with medicinal properties (Thuc et al, 2020).…”
Section: Description Of Several Species Of Edible Mushrooms Descripti...mentioning
confidence: 99%
“…Volvariella volvacea (Bulliard ex Fries) Singer, 1951, also known as "rice mushroom", "straw fungus" or "Chinese mushroom", is a species found in tropical and subtropical climates (Liu et al, 2020). Its cultivation is believed to have originated in China, possibly before the 18th century (Chang, 1977), and has been used due to its high concentrations of nutrients and bioactive compounds with medicinal properties (Thuc et al, 2020).…”
Section: Description Of Several Species Of Edible Mushrooms Descripti...mentioning
confidence: 99%
“…Transcriptome analysis of the three developmental stages of Wolfiporia cocos revealed that peroxisome, unsaturation of fatty acids, and degradation pathway were respectively prevalent in three stages [ 10 ]. A comparative transcriptomics study between two commercially available Volvariella volvacea strains, V9 and V26, identified various candidate genes involved in the fast growth requirement of V. volvacea , which provided a valuable resource for strain improvement of this commercially edible mushroom [ 11 ]. A. auricula has a stronger selenium accumulation ability, and comparative transcriptomics analysis between its mycelia collected from ordinary medium and medium containing 100 μg/g selenium identified the genes and metabolic pathways related to selenium accumulation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Volvariella volvacea (Bull.) Singer, también conocida como "seta del arroz", "hongo de la paja" o "Chinese mushroom" es una especie de climas tropicales y subtropicales (Liu et al, 2020). Su cultivo se habría originado en China, presumiblemente antes del siglo XVIII (Chang, 1977), aprovechando sus elevadas concentraciones de nutrientes y compuestos bioactivos con propiedades medicinales (Chen et al, 2019;Thuc et al, 2020).…”
Section: Introductionunclassified